Nanostructured perovskite oxides for dye-sensitized solar cells. (22nd September 2021) - Sheikh, Md Sariful; Roy, Anurag; Dutta, Alo; Sundaram, Senthilarasu; Mallick, Tapas K; Sinha, T P
Abstract: Since its discovery, the dye-sensitized solar cell (DSSC) technology with its low-cost, simple fabrication procedure and promising photovoltaic (PV) performance remains a fertile research topic. Most DSSC research is focused on the TiO2, ZnO and other binary metal oxides based photoelectrodes and costly platinum (Pt) based counter electrodes (CEs). However, the overall PV performance of these traditional DSSCs is still inadequate compared to other standard PV technologies. The nanostructured perovskite oxides (POs) with their easily tunable interesting photophysical properties, higher stability, relatively simple synthesis procedure and high PV performance emerge as the promising alternatives for the binary metal oxide-based photoelectrodes and costly Pt-based CEs. Though there has been significant improvement in inorganic PO photoanode and CE based DSSCs in the last decade, a combined report on it is still missing. This review reports the underlying mechanisms, latest advances, and prospects of the PO photoanodes and CEs, with a particular focus on PO-based transparent conductive electrodes. We have summarized the shortcomings of the conventional DSSCs and highlighted the potentials of POs to overcome those limiting factors, which will guide the rational design of a highly efficient, cost-effective, and stable DSSC.